Nanostructured Lipid Carriers in Drug Delivery: A Review - Tikam, Shruti; Pomaje, Madan; Patil, Ashwini; Kamat, Viraj; Bhagwat, Ruchita (International Journal of Membrane Science and Technology, 2023)
Over the past 20 years, lipid-based colloidal systems have gained attention as a means of delivering medications that are not readily soluble in water. The research that has been done has centred on creating various formulations with a broad range of active molecules and excipients. On the particle structure of these colloidal systems, there is disagreement, though. This is partially because there haven’t been many studies focused on understanding the drug’s preferred location within the particle as well as the arrangement of lipids and stabilising agents during particle formation. This review presents the most widely used materials and preparation techniques for obtaining lipid particles as a contribution in this regard. Additionally, scientometrics tools are used in the synthesis and analysis of the particle characteristics, such as shape, size and distribution, zeta potential, drug loading capacity, and drug entrapment efficiency. A simulation of particle framework based on the creation of the various polymorphic forms of the solid lipid due to the initial ingredients and processing circumstances is proposed in along with the existing evidence. In general, the significance of gaining a thorough understanding of the lipid nanoparticles’ structure is emphasised, as this is helpful for the logical design of these nanocarriers.